Impact of percent body fat on specific ability - Algerian soccer players - Zerf, M. (Serbian Journal of Sports Sciences, 2016)
Performance in soccer is dependent upon many factors, including those technical, tactical, mental and physiological. All similar studies confirm that fitness in soccer-specific context refers to a range of individual characteristics, and that lower body fat percentage is an advantage both physically and metabolically in soccer competitions. Similar studies have confirmed that the muscle and the fat components show an equally slight positive correlation with the age increase of 1 year [1], while the required lower percent body fat must be less than 2.0% for a soccer-specific fitness [2]. For the purpose, our sample were first division players from league Oran in year 2014-2015. Represented by 57 male players, their average age 24±1.02, with a career that exceeds eight years, their homogeneity was calculated based on BFP categories ratio. It was tested on anthropometric parameter and most athletic performance in a soccer game, to determine the impact of PFP on ability of Algerian soccer players and to predict the most specific ability affected by this. We concluded that: A) More body fat percent influenced parameters both physical and anthropometric. B) Most physical qualities affected by BFP are recorded in the ability of repeated rapid series (change of direction) and continuous long distances.